Comparative Outcomes of Ligation of the Intersphincteric Fistula Tract (LIFT) Versus Seton Placement in the Management of Fistula-in-Ano - Muhammad Hamza Shafi, Syeda Samina Ashfaq, Jawad Ahmed, Muhammad Azhar Qureshi, Farhan Ali, Muhammad Rashid Waheed, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Fistula-in-ano is a common surgical problem with significant morbidity. Management of this includes the widely used Ligation of Intersphincteric Fistula Tract (LIFT) procedure and the LIFT Seton technique. The Seton technique is a conventional one but LIFT is minimally invasive and sphincter preserving. Objective: Analysis of healing time and postoperative pain with LIFT vs. Seton for patients with fistula in ano. Material and Methods: The present randomized controlled trial was conducted at Department of General surgery NISHTAR HOSPITAL MULTAN during April 2022 to March 2023. There were 106 patient diagnosed with fistula-in-ano randomized to the LIFT group (n = 53) or the Seton group (n = 53). Descriptive data of age, fistula duration, height, weight, healing time and post operative pain were collected. The healing time was measured in weeks and the postoperative pain was graded with the help of the Visual Analog Scale (VAS). All data were analysed using SPSS version 25 and p<0.05 was considered statistically significant. Results: Mean healing time was shorter in the LIFT group (4.83 weeks, SD = 0.504) than in the Seton group (9.93 weeks, SD = 1.115; p < 0.001). In the LIFT group postoperative pain was significantly lower (4.22, SD = 1.111) than in the Seton group (5.22, SD = 1.368; p < 0.001). Conclusion: The LIFT procedure results in faster healing time and less post-operative pain when compared with Seton procedure, and is thus favored for managing fistula in ano. Keywords: LIFT procedure,Post-operative pain, Fistula-in-ano, Seton procedure, Healing time, Surgical outcomes